Pitching sebagai Kompetensi Komunikasi Strategis SDM untuk Membangun Kepercayaan dalam Negosiasi Bisnis Digital - Refania Hafifah; Selvy Afrioza (MAMEN: Jurnal Manajemen, 2026)
Abstract The growth of the digital business landscape requires human resources to possess strategic communication skills that enable them to convey ideas, business values, and competitive advantages in a convincing manner. One form of communication that is becoming increasingly relevant in this context is pitching. Pitching is understood as a brief presentation activity and a strategic HR competency in building trust, shaping perceptions, and strengthening bargaining positions in digital business negotiations. The purpose of this study is to analyze pitching as a strategic communication competency of HR in building trust during digital business negotiation processes. This study employs a qualitative approach using a literature review method. Data were obtained from various scholarly sources, including scientific journals, books, and academic articles relevant to the topics of pitching, strategic communication, HR competencies, trust, negotiation, and digital business. Data analysis was conducted using a descriptive-analytical approach through the processes of identification, classification, synthesis, and interpretation of the literature. The results of the study indicate that pitching plays a crucial role in conveying value propositions, establishing the communicator’s credibility, creating initial trust, and opening avenues for dialogue in digital business negotiations. The effectiveness of pitching is influenced by message clarity, a systematic delivery structure, understanding the audience, emphasizing benefits, and the appropriate use of digital media. This study makes a conceptual contribution by positioning pitching as a strategic communication competency for human resources—not merely a presentation tool, but a crucial instrument for building trust and supporting the success of digital business negotiations. Keywords: Pitching, Strategic Communication Competency, Human Resources, Trust, Digital Business Negotiations Abstrak Perkembangan bisnis digital menuntut sumber daya manusia memiliki kompetensi komunikasi strategis yang mampu menyampaikan ide, nilai bisnis, dan keunggulan kompetitif secara meyakinkan. Salah satu bentuk komunikasi yang semakin relevan dalam konteks tersebut adalah pitching. Pitching dipahami sebagai aktivitas presentasi singkat, kemampuan strategis SDM dalam membangun kepercayaan, membentuk persepsi, dan memperkuat posisi tawar dalam negosiasi bisnis digital. Tujuan penelitian untuk menganalisis pitching sebagai kompetensi komunikasi strategis SDM dalam membangun kepercayaan pada proses negosiasi bisnis digital. Penelitian ini menggunakan pendekatan kualitatif dengan metode literature review. Data diperoleh dari berbagai sumber pustaka berupa jurnal ilmiah, buku, dan artikel akademik yang relevan dengan topik pitching, komunikasi strategis, kompetensi SDM, kepercayaan, negosiasi, dan bisnis digital. Analisis data dilakukan secara deskriptif analitis melalui proses identifikasi, klasifikasi, sintesis, dan interpretasi literatur. Hasil kajian menunjukkan bahwa pitching berperan penting dalam menyampaikan proposisi nilai, membangun kredibilitas komunikator, menciptakan kepercayaan awal, serta membuka ruang dialog dalam negosiasi bisnis digital. Efektivitas pitching dipengaruhi oleh kejelasan pesan, struktur penyampaian yang sistematis, pemahaman terhadap audiens, penekanan pada manfaat, serta pemanfaatan media digital secara tepat. Penelitian ini memberikan kontribusi konseptual dengan menempatkan pitching sebagai kompetensi komunikasi strategis SDM, bukan sekadar alat presentasi, melainkan instrumen penting dalam membangun kepercayaan dan mendukung keberhasilan negosiasi bisnis digital. Kata kunci: Pitching, Kompetensi Komunikasi Strategis, Sumber Daya Manusia, Kepercayaan, Negosiasi Bisnis Digital